A Antropofagia Indiana na Obra de Amitav Ghosh / The Indian “Anthropophagy” in the Amitav Ghosh’s Works In an Antique Land and Calcutta Chromosome - Lemos, Gisele Cardoso de (Numen, 2012)
<!–st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:"Times New Roman"; > <! [endif] > Resumo Amitav Ghosh, escritor e intelectual indiano, proporciona ao leitor por meio de sua prática literária obras espiritualizadas, no sentido em que Partha Chatterjee percebe a divisão das práticas e instituições sociais da Índia, como uma das possibilidades geradas pelo nacionalismo, ou seja, a presença de dois domínios: o “domínio material” e o “domínio espiritual”. Essa conceituação busca uma instrumentalização do estereótipo indiano de espiritualidade criado pelo orientalismo europeu como recurso para, dentre outras coisas, criar uma arte moderna sem ser ocidental, também pautada na releitura das tradições endógenas. Ghosh, então, demonstra uma habilidade singular nessa arte. Palavras-chave: Amitav Ghosh; Literatura indiana; Pós-colonialismo; Espiritualidade. Abstract Amitav Ghosh, Indian writer and intellectual, gives the reader through his literary practice spiritualized works, in the sense that Partha Chatterjee sees the division of social practice and institution spheres of India as one of the possibilities generated by nationalism, which means the presence of two areas: the “material domain” and “spiritual domain”. These concepts seek a manipulation of the stereotype of Indian spirituality created by the European orientalism as a resource for creating a modern art without being Western, also based in the reassessment of local traditions. Ghosh then shows a unique ability in this art. Keywords: Amitav Ghosh; Indian literature; Postcolonialism; Spirituality. </bo–>